1082. Real-World Experience with Omadacycline for Nontuberculous Mycobacterial Infections: A Multicenter Evaluation. (4th December 2021) - Morrisette, Taylor; Alosaimy, Sara; Lagnf, Abdalhamid M; Philley, Julie V; Sigler, Carly; Butt, Saira; Kaip, Emily A; MacDougall, Conan; Mejia-Chew, Carlos; Bouchard, Jeannette; Frens, Jeremy J; Gore, Tristan; et al.
Abstract: Background: Nontuberculous mycobacteria (NTM) are resistant to numerous antibiotics and lead to significant morbidity and mortality. Omadacycline (OMC) is an aminomethylcycline antibiotic that is Food and Drug Administration-approved for acute bacterial skin and skin structure infections and community-acquired bacterial pneumonia. Furthermore, OMC has shown in vitro activity against NTM. Given that real-world evidence is lacking, our primary objective was to evaluate the clinical success and tolerability of OMC when used for a variety of NTM infections. Methods: This was a multicenter, retrospective, observational study conducted from January 2020 to June 2021. We included all patients ≥ 18 years of age that received OMC of any indication for Mycobacterium spp. The primary outcome was clinical success, defined as a lack of all-cause mortality, lack of persistence or re-emergence of infection during or after therapy, and lack of alteration of OMC. Incidence of adverse effects potentially attributable to OMC and reasons for OMC utilization were also analyzed. Results: A total of 31 patients were included from 12 geographically distinct academic health systems (median age: 57 (IQR, 45-63) years; 45% male; 81% Caucasian). The majority of isolated pathogens were Mycobacterium abscessus complex (84%) and of those with subspeciation performed (54%), the majority (86%) were subsp. abscessus . The primary infections were of pulmonary origin (67%) and the median (IQR) duration of OMC therapy was 5.3 (3.2-9.4) months. Most isolates did not have OMC susceptibility conducted (87%), while the majority did for tigecycline (90%). Clinical success was reported in 81% of the population. Most patients were on combination antimicrobial therapy, and 39% of patients reported an adverse effect while on OMC (58% gastrointestinal distress). The majority of patients were prescribed OMC due to ease of administration (61%) and antimicrobial resistance to previous antibiotics (42%). Conclusion: OMC may be a potential option for the therapy of NTM infections. Prospective, randomized clinical trials are needed to confirm our preliminary findings. Disclosures: Julie V. Philley, MD, Paratek Pharmaceuticals (Advisor or Review Panel member)Paratek Pharmaceuticals, Inc. (Consultant) Michael P. Veve, Pharm.D., Cumberland (Grant/Research Support)Paratek Pharmaceuticals (Research Grant or Support) Michael J. Rybak, PharmD, MPH, PhD, Paratek Pharmaceuticals (Research Grant or Support)